1998
DOI: 10.1046/j.1523-536x.1998.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Peer Counselors Increase Breastfeeding Duration Among Rural Low‐Income Women

Abstract: A volunteer peer counseling program that provides low-income women with role models, accurate information, support, and encouragement can increase the duration of breastfeeding, and thus contribute to healthier infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
105
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 20 publications
6
105
2
Order By: Relevance
“…The evidence about the long-term impact of peer counseling on prevalence of breast-feeding is mixed (14)(15)(16). In an exhaustive review of the literature, Fairbank and colleagues (16) have noted that peer support programs delivered in the antenatal and postnatal periods have been associated with increased initiation and duration of breast-feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence about the long-term impact of peer counseling on prevalence of breast-feeding is mixed (14)(15)(16). In an exhaustive review of the literature, Fairbank and colleagues (16) have noted that peer support programs delivered in the antenatal and postnatal periods have been associated with increased initiation and duration of breast-feeding.…”
Section: Discussionmentioning
confidence: 99%
“…3 Numerous observational studies have reported increases in breastfeeding initiation and duration associated with peer counseling programs for WIC clients. [4][5][6][7][8][9][10][11][12] The common approach in these studies has been to compare the outcomes of WIC clients in LWAs with and without a peer counseling program. 4,5,6,8,12 A systematic literature review of peer counseling initiatives has characterized many of these observational studies as being of moderate to poor quality.…”
mentioning
confidence: 99%
“…Studies have shown that availability of trained personnel/ peer counselor can significantly improve breastfeeding initiation and duration in rural, low income population. [11][12][13][14][15] Role of nurses as health care worker for successful implementation of breastfeeding cannot be understated. 16 Studies have emphasized the need to adequately train the health care staff for successful breast feeding.…”
Section: Discussionmentioning
confidence: 99%